Feeding Problems in Children with Congenital Heart Diseases in Nasiriya Heart Center - Wishel, oday; malaa, Eqbal (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To identify feeding problems of children with congenital heart disease. Methodology: Non probability (purposive) sample of (65) were selected of 225 children who visit Al Nasiriya heart center during the period of conducting the pilot study, previously diagnosed with congenital heart disease. Results: The study results indicated that children with congenital heart disease have feeding difficulties, low birth weight , repeated diarrhea , more than half of the sample taking medication for heart disease which cause repeated vomiting, difficulty taking liquids and refusal of feeding or eating.(64.6%) of study sample suffered from wasting. (78.5%) suffered from stunting. Almost half of the study sample suffered from malnutrition (49.2%). Recommendation: The study recommended an establishment of feeding unit, located at heart disease hospitals and health centers, to teach the families the methods of feeding through teaching program for the purpose of raising their awareness about child’s feeding problems.